2022
DOI: 10.1002/mana.202000102
|View full text |Cite
|
Sign up to set email alerts
|

Lineability, algebrability, and sequences of random variables

Abstract: We show that, when omitting one condition in several well‐known convergence results from probability and measure theory (such as the Dominated Convergence Theorem, Fatou's Lemma, or the Strong Law of Large Numbers), we can construct “very large” (in terms of the cardinality of their systems of generators) spaces and algebras of counterexamples. Moreover, we show that on the probability space false(false[0,1false],scriptBfalse(false[0,1false]false),λfalse)$([0,1],\mathcal {B}([0,1]),\lambda )$ the families of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The first result goes deeper into the study of [33, theorem 5.2.1], where it is shown that the family D 0 is ℵ 0 -lineable. To do so, we begin by recalling a theorem from number theory and dynamical systems known as Kronecker's density theorem (see, for instance, [20,28,30]).…”
Section: Derivatives With Special Propertiesmentioning
confidence: 99%
“…The first result goes deeper into the study of [33, theorem 5.2.1], where it is shown that the family D 0 is ℵ 0 -lineable. To do so, we begin by recalling a theorem from number theory and dynamical systems known as Kronecker's density theorem (see, for instance, [20,28,30]).…”
Section: Derivatives With Special Propertiesmentioning
confidence: 99%
“…Also, let us present the notion of latticeable (introduced in [19] and later studied in [7,15]). Before that, recall that a Riesz space, also called a vector lattice, is a partially ordered (with, say, the order ) vector space X where the order structure is a lattice.…”
Section: Preliminary Notions and Notationsmentioning
confidence: 99%